2018
DOI: 10.1017/s0266466618000051
|View full text |Cite
|
Sign up to set email alerts
|

Asymptotic Theory for Estimating Drift Parameters in the Fractional Vasicek Model

Abstract: This article develops an asymptotic theory for estimators of two parameters in the drift function in the fractional Vasicek model when a continuous record of observations is available. The fractional Vasicek model with long-range dependence is assumed to be driven by a fractional Brownian motion with the Hurst parameter greater than or equal to one half. It is shown that, when the Hurst parameter is known, the asymptotic theory for the persistence parameter depends critically on its sign, corresponding asympto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
27
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(28 citation statements)
references
References 49 publications
1
27
0
Order By: Relevance
“…It was demonstrated there that asymptotic normality is violated for H > 3 4 . Similar approach used in more general setting of the fractional Vasicek model was presented in [26] and [27], where both ergodic and non-ergodic cases are considered. Recently, the 4 th moment theorem was successfully utilized to demonstrate not only asymptotic normality, but also to establish the speed of the convergence to the normal distribution (Berry-Esseentype of bounds) of the MC estimator of the drift parameter in one-dimensional SDEs driven by fBm -see [11] for discrete-time observations with increasing time-horizon and fixed mesh or [24] for continuous-time observations or discrete-time observations with combination of increasing time-horizon and observation frequency.…”
Section: Introductionmentioning
confidence: 99%
“…It was demonstrated there that asymptotic normality is violated for H > 3 4 . Similar approach used in more general setting of the fractional Vasicek model was presented in [26] and [27], where both ergodic and non-ergodic cases are considered. Recently, the 4 th moment theorem was successfully utilized to demonstrate not only asymptotic normality, but also to establish the speed of the convergence to the normal distribution (Berry-Esseentype of bounds) of the MC estimator of the drift parameter in one-dimensional SDEs driven by fBm -see [11] for discrete-time observations with increasing time-horizon and fixed mesh or [24] for continuous-time observations or discrete-time observations with combination of increasing time-horizon and observation frequency.…”
Section: Introductionmentioning
confidence: 99%
“…In the general case, the least squares and ergodic-type estimators of unknown parameters α and β were studied in [27,38,39]. The corresponding MLEs of α and β were presented in [25].…”
Section: Introductionmentioning
confidence: 99%
“…Prakasa Rao [4] gave an extensive review on most of the recent developments related to the parametric and other inference procedures for stochastic models driven by fBm. The latest study can be found in Xiao and Yu [5,6], who developed the asymptotic theory for least square estimators for two parameters in the drift function in the fractional Vasicek model with a continuous record of observations. Another possibility is to use Euler-type approximations for the solution of the above equation and to construct an MLE estimator based on the density of the observations given "the past", for the case of stochastic equations driven by Brownian motion.…”
Section: Introductionmentioning
confidence: 99%